2014
DOI: 10.9738/intsurg-d-13-00146.1
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Oral Feeding as Early as One Day After Elective Surgery for Colorectal Cancer: Oral Feeding on First Versus Second Postoperative Day

Abstract: The optimal timing of early oral intake after surgery has not been fully established. The objective of this study was to compare early oral intake at postoperative day 1 after resection of colorectal cancer with that of day 2 to identify the optimal timing for resumption of oral intake in such patients. Consecutive patients with colorectal cancer who underwent elective colorectal resection were separated into two groups. Sixty-two patients began a liquid diet on the first postoperative day (POD1 group) and 58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 19 publications
5
35
0
2
Order By: Relevance
“…The present study aimed to investigate postoperative feeding practices among hospitalised patients. Although early oral feeding is a strategy that can contribute to improved recovery and reduced complications after surgery ( 1,5,6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) , it does not appear to be commonly applied in clinical practice. Of the 29 studies meeting the inclusion criteria, only 40% and 22% reported time to first feed and time to first solid feed in-line with evidenced-based recommendations, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study aimed to investigate postoperative feeding practices among hospitalised patients. Although early oral feeding is a strategy that can contribute to improved recovery and reduced complications after surgery ( 1,5,6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) , it does not appear to be commonly applied in clinical practice. Of the 29 studies meeting the inclusion criteria, only 40% and 22% reported time to first feed and time to first solid feed in-line with evidenced-based recommendations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Early oral feeding has been associated with a faster recovery of intestinal function (i.e. resolution of ileus) (5,6,9,10,19,20) , reduced morbidity (e.g. less infectious complications and improved wound healing and immunity) (5,(11)(12)(13)15,21,22) and improved quality of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, colorectal surgeons have been hesitant to feed their patients immediately after surgery . Traditional postoperative practices restrict food and beverages, in theory to help reduce surgical complications, including the development of a paralytic ileus, potential aspiration pneumonia, and breakdown of the surgical anastomosis .…”
Section: Introductionmentioning
confidence: 99%
“…Historically, colorectal surgeons have been hesitant to feed their patients immediately after surgery . Traditional postoperative practices restrict food and beverages, in theory to help reduce surgical complications, including the development of a paralytic ileus, potential aspiration pneumonia, and breakdown of the surgical anastomosis . The surgical team has typically waited until the patient passes flatus or has a bowel movement and there are no signs of nausea, vomiting, or abdominal distention before allowing patients to eat by mouth .…”
Section: Introductionmentioning
confidence: 99%
“…Early oral feeding after gastric oncological surgery seems feasible and safe, and should be started at the day of surgery, irrespective of the extent of the gastric resection and the type of surgery [75]. This also applies to early nutrition following colorectal resections, as results show that this practice is safe and feasible [76].…”
Section: Nutritional Supportmentioning
confidence: 99%